Employee empowerment and empowering leadership: A literature review - Vu, Hieu Minh (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Empowerment fosters employee’s creativity, quality of work-life, spirit of teamwork and organisational effectiveness. organisations do not only need to empower employees but should also encourage empowering leadership. Empowering leadership connotes the sharing of power and motivating employees to crave for superior performance. This paper focuses on literature in the employee empowerment and empowering leadership contexts. Considering the role people play in organisations, it is important to understand the impact of employee empowerment and empowering leadership on organisational outcomes. The author used historical data and findings from previous studies to draw insight on the subject. Based on our review, it was observed that employee empowerment fosters employee performance, job satisfaction, organisational commitment, customer satisfaction, productivity and business growth. Empowering leadership have been examined from the structural and motivational theoretical perspective. Several studies lend credence to the positive influence of empowering leadership on employees’ psychological empowerment. The author proposed some recommendations for managers to implement